The Effect of the SAMR Model on Acquiring Teaching Skills for Students of Colleges of Education in the Subject of Teaching Applications - Radhi, Ruaa Ibrahem; Abdulsalam Sabri, Dr. Dawood (International journal of early childhood special education, 2021)
This research aims to identify the impact of the model (SAMR) in acquiring teaching skills among students of the colleges of education in the subject of teaching applications. The research sample consisted of (50) students selected from the department of educational and psychological sciences in the College of Education Ibn Rushd For the academic year (2020-2021). This was then divided in a simple random fashion into two groups: the first group (experimental group) included (25) students trained in scientific education lessons according to the teaching program prepared for it while the second group (control group) included (25) students. The researchers conducted the process of balance between the two groups in a number of variables to achieve a goal and choose its hypotheses. After collecting, analysing and processing data statistically using the statistical package (SPSS) and performing t-test on two independent samples and the equation of the ETA box to measure the size of the effect, we obtained the following results: There is no statistically significant difference at the level of significance (0.5) between the average grades of students of the experimental group and the control group in acquiring teaching skills for the experimental group. In light of the findings, the researchers reached several conclusions and presented several recommendations and suggested several future studies.